Synthesis of sec.-undecylbenzene and sec.-dodecyl benzene by alkylation (Bangladesh Journal of Scientific and Industrial Research, 2014)
The title compounds were synthesized by the alkylation of benzene with olefins (undecene-1 and dodecene-1) in presence of borontrifluoride etherate and alcohols (undecan-1- ol and dodecan-1- ol) with anhydrous AlCl3. The effect of temperature, molar ratio of benzene to olefins & alcohols, amount of catalyst were studied. The highest yield was 73.6% in case of dodecene-1 and in case of undecene-1 was 70.6%. Dodecan-1-ol was found to be more reactive than undecanl-1-ol but the yields were higher in olefins than alcohols. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18848 Bangladesh J. Sci. Ind. Res. 49(1), 9-12, 2014